Eksperimen Teknik Contract Learning dalam Mengatasi Perilaku Membolos Siswa SMA - Keysa Aurelia Pandiangan; Endang Setyaningsih (Indo Publishing, 2026)
Truancy is a chronic form of maladaptive behavior in Senior High Schools (SMA) that adversely affects students' academic performance and discipline. This study aims to empirically examine the effectiveness of implementing Contract Learning (behavior contracting) techniques in reducing the frequency of truancy among high school students. A quantitative approach with a quasi-experimental method using a One-Group Pretest-Posttest Design was employed. The research subjects consisted of 10 eleventh-grade high school students selected through purposive sampling based on the severity of unexcused absences (a minimum of 5 truant episodes within the past month). Daily data collection utilized the Student Attendance Monitoring Sheet (LPKS) and the Truancy Behavior Scale. The intervention was conducted individually over 4 sessions, focusing on behavior analysis, written contract negotiation, autonomous selection of positive reinforcement, and periodic monitoring. Data were analyzed using the non-parametric statistical technique, the Wilcoxon Signed-Rank Test. The results indicated a highly significant decrease in the average frequency of truancy, dropping from 6.7 times in the pretest phase to 0.8 times in the posttest phase. The hypothesis testing yielded a statistical value of Z = -2.805 with a significance level of 0.005 (p < 0.05), thereby accepting the alternative hypothesis. The Contract Learning technique is proven to be significantly effective in reducing truancy rates by enhancing students' self-regulation, personal accountability, and intrinsic motivation. Obstacles during the intervention involved external factors such as low parental supervision and peer pressure. Therefore, it is highly recommended for Guidance and Counseling teachers to integrate parental control into future implementations of behavior contracts.